PENGARUH RASIO PROFITABILITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN FOOD AND BAVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 – 2020 - Almaas Kurnia Savira; Andi Iswoyo (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to examine the effect of profitability ratios with the Return On Assets indicator, liquidity with the Cash Ratio indicators and solvency with the Debt to Asset Ratio indicators on dividend policy in food and baverage companies listed on the Indonesia Stock Exchange 2016 – 2020. This research is a quantitative research. The population of this research is all food and beverage companies listed on the Indonesia Stock Exchange 2016 – 2020. The determination of the sample in this study uses the purposive sampling method. So that obtained 64 samples in this study. The method used is the method of multiple linear analysis. Based on the results of multiple regression with a significant level of 5%, the results of this study conclude: (1) Profitability has a significant effect on dividend policy. (2) Liquidity has no significant effect on dividend policy. (3) Solvency has no significant effect on dividend policy. (4) Profitability, Liquidity and Solvency have no simultaneous effect on dividend policy.